Improving Reading Comprehension of EFL Learners through Metacognitive Strategies - Bonganciso, Ruel; Bonganciso, Jade M. (Journal of World Englishes and Educational Practices, 2022)
Reading comprehension is one of the core learning abilities that plenty of learners struggle with. Being an active process of reading and extracting meaning from text, this cognitive skill requires effective use of strategic processes. To help the learners perform better in reading comprehension, action research, which aims to identify the effects of metacognitive strategies on the reading comprehension level of the thirty-three  Grade-7 L2 learners, was conducted. A validated researcher-made reading comprehension test, observation checklist, and interview guide were used to gather the data. Results show that the reading comprehension level of the learners is average in the pretest and above average in the posttest. As observed, the learners were active while reading the text by making annotations on the text they were reading. Most of them said that they were able to monitor their comprehension by asking questions and making predictions while reading the text. Thus, there is an increase in the reading comprehension performance of the learners after the intervention. Accordingly, metacognitive strategies are useful in developing the reading comprehension performance of the learners.